2012
DOI: 10.1016/j.brat.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring sudden gains in behavioral activation therapy for Major Depressive Disorder

Abstract: Understanding the onset and course of sudden gains in treatment provides clinical information to the patient and clinician, and encourages clinicians to strive for these sudden clinical gains with their patients. This study characterizes the occurrence of sudden gains with Behavioral Activation (BA; Martell, Addis, & Jacobson, 2001), and the extent to which pre-treatment dysfunctional depressive thinking predicts sudden gains during treatment. We enrolled a sample of adults (n = 42) between ages 18–65 diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 41 publications
(128 reference statements)
11
39
0
1
Order By: Relevance
“…We found that 42.5% of participants receiving behavioural activation experienced sudden gains and that those experiencing sudden gains had better outcomes posttreatment than those who did not. The rates of sudden gains in our study are similar to those found in the samples of Hopko et al (2009;50%) and Hunnicutt-Ferguson et al (2012;35.7%). These rates are similar to those originally reported for CBT for depression by Tang and DeRubeis (1999;39%) despite the difference in the length of therapy offered (up to 12 sessions in the current study cf.…”
Section: Sudden Gain Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…We found that 42.5% of participants receiving behavioural activation experienced sudden gains and that those experiencing sudden gains had better outcomes posttreatment than those who did not. The rates of sudden gains in our study are similar to those found in the samples of Hopko et al (2009;50%) and Hunnicutt-Ferguson et al (2012;35.7%). These rates are similar to those originally reported for CBT for depression by Tang and DeRubeis (1999;39%) despite the difference in the length of therapy offered (up to 12 sessions in the current study cf.…”
Section: Sudden Gain Characteristicssupporting
confidence: 89%
“…The current study examines post-treatment outcome, but does not establish whether sudden gains are linked to improved outcome at follow-up. Whilst Hopko et al's (2009) study showed that those participants with sudden gains had improved outcomes at 3 months follow up, neither Hunnicutt-Ferguson et al (2012) nor the current study include follow up data, so this finding needs to be replicated and extended. The stability of the relationship between gain and outcome has been shown at follow up after CBT for depression (Hardy et al, 2005) but is less clear in the longer term (Tang et al, 2002).…”
Section: Limitations Future Directions and Conclusionmentioning
confidence: 67%
“…Although there is some support for this assumption coming from treatment studies for depression (e.g. Tang & DeRubeis, 1999; Tang et al, 2005), cognitive change was not predictive of SGs in studies examining behavioural activation (Hunnicutt-Ferguson, Hoxha, & Gollan, 2012) or supportive-expressive therapy for depression (Andrusyna, Luborsky, Pham, & Tang, 2006) or CBT for social anxiety disorder (Hofmann, Schulz, Meuret, Moscovitch, & Suvak, 2006; Bohn, Aderka, Schreiber, Stangier, & Hofmann, 2013). It is possible that SGs are more likely to emerge as treatment mediators in interventions that place a relatively great focus on modifying maladaptive beliefs, such as CBT for depression as compared to other treatments, such as those that are focused on an exposure-extinction paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…As early as the 1980s, psychotherapy researchers have observed that the bulk of symptomatic improvement occurs within the 1st month of therapy, with 60% of total improvement in cognitive behavioral therapy for depression occurring by Week 4 (Rush, Kovacs, Beck, Weissenburger, & Hollon, ). Since then, numerous other studies have reported early response patterns across different mental health problems and psychological therapies (Bell, Waller, Shafran, & Delgadillo, ; Bradford et al, ; Delgadillo et al, ; Doyle, Le Grange, Loeb, Doyle, & Crosby, ; Gois et al, ; Hunnicutt‐Ferguson, Hoxha, & Gollan, ; Rubel et al, ).…”
Section: Introductionmentioning
confidence: 99%